Three dimensional flow of liquid transfer between a cavity and a moving roll - Campana, Diego Martin (2016)
Gravure printing is one of the most promising technologies for high volume production of printed electronics and microscale films and devices. The characteristics of the printed pattern, i.e. ink volume, resolution and pattern placement (registration), are directly related to the fluid mechanics of the liquid transfer process from a cell to a substrate wrapped around a rotating roll; the liquid transfer is mainly controlled by free surfaces and dynamic contact lines. Most of the available analyses are restricted to axisymmetric flows, at which the relative motion between the cavity and the substrate is greatly simplified. Recent results have shown that the use of the complete description of the relative motion in a roll-to-roll process is critical to obtain accurate results on the amount of liquid that is transferred to the substrate. In this work we present an extension of the model describing liquid transfer from a groove to a substrate in a R2R process in order to consider the liquid transfer from a small individual cell; to this end we solve a full 3D free surface flow with moving contact lines. The results show that the liquid transfer dynamics is governed by two different characteristic time scales, one is associated with the contact line motion and the other with liquid filament breakup. Both are dependent on the capillary number. The predictions show how the volume, registration and shape of the printed dot varies with operating conditions and liquid properties. These predictions could be helpful in designing high precision printing operations.